2020
DOI: 10.3390/agronomy10030365
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fresh Scotta Whey as an Additive for Alfalfa Silage

Abstract: Scotta is a dairy industry waste obtained by ricotta cheese production. Because of its high availability and its high lactose content, scotta could be used as an additive to improve fermentation characteristics of alfalfa silage. Silage samples were obtained for 2 years from an alfalfa second cut, collecting the forage at three growth stages: mid bud (MB), early flowering (EF), and late flowering (LF). After wilting the forage at 38% dry matter (DM), four scotta doses were added (0, 75, 150, and 300 g/kg fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Furthermore, Cajarville et al [26] reported that the use of fresh cheese whey in the ensilage of temperate forages is desirable, as it increases the DM degradability. Mariotti et al [27] used whey obtained by ricotta cheese production, which has got a high lactose content. The addition of ricotta whey decreased the pH and fiber fractions, increased the relative feed value and had no effect on the crude protein concentration or the total digestible nutrients.…”
Section: Results On the Application Of The Developed Bioactive Silage By Inclusion In Broilers Nutritionmentioning
confidence: 99%
“…Furthermore, Cajarville et al [26] reported that the use of fresh cheese whey in the ensilage of temperate forages is desirable, as it increases the DM degradability. Mariotti et al [27] used whey obtained by ricotta cheese production, which has got a high lactose content. The addition of ricotta whey decreased the pH and fiber fractions, increased the relative feed value and had no effect on the crude protein concentration or the total digestible nutrients.…”
Section: Results On the Application Of The Developed Bioactive Silage By Inclusion In Broilers Nutritionmentioning
confidence: 99%
“…It contains high content of lactose (69-76%), low content of water (<7%) and is rich in protein (β-lactoglobulin and α-lactalbumin), vitamins (B 2 , B 5 and C) and minerals (EWPA, 2016). Each year, more than 200 mln t of whey is generated globally, and this value is increasing by ~2% each year (Mariotti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Acid whey is a dairy industry waste obtained from cheese production [25] for which the industry has long tried to find a sustainable utilization [26]. The increased demand for dairy products creates an excessive supply of acid whey (approximately 9 kg of whey per kilogram of cheese) that must be either disposed of or repurposed [27].…”
Section: Introductionmentioning
confidence: 99%